Public Conflicts and Trust - Kim, Dong Young (Understanding the Drivers of Trust in Government Institutions in Korea, 2018)
This chapter explores the relationship between public conflicts and institutional trust* in Korea. It emphasizes that the lack of effective mechanisms to prevent and resolve frequent and prolonged public conflicts in Korea may have generated a climate of distrust and animosity. In turn, based on evidence from the OECD-KDI survey, it argues that by endorsing innovative forms of conflict management such as sharing information on controversial policy issues before a decision is made, consulting public opinions early on and incorporating such opinions in the final decision, engaging relevant stakeholders in the creation of solutions, and finding facts jointly with stakeholders, a virtuous cycle transforming relations between citizens and public institutions from adversarial into collaborative could be created.